Pengaruh Kinerja Keuangan Terhadap Harga Saham - Supriadi, Yoyon; Ariffin, Muhammad (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
Stock is an investment instrument which is prefered at the present. Basically, the purpose of investing in stock field is to get capital gain or investment rate return at high stage. Financial performance is a standard to find out the condition of a company based on its annual financial statement. Financial condition can be taken note of by making use of financial ratio analysis. The author utilizes Earning per Share, Return on Assets, and Operating Profit Margin to know the financial performance. The purpose of this research is to find out the impact of financial performance on stock price. The author knows the financial performance from EPS (X1), ROA (X2), and OPM (X3) of Stock Price (Y). EPS, ROA, and OPM are taken by the author from performance summary originated in IDX. The research was conducted during the period 2006 through 2010 by taking samples at PT Indocement Tunggal Prakarsa Tbk. and PT Holcim Indonesia Tbk engaged in basic industry, that is cement industry. Based on the result of this research, it can be concluded that just Operating Profit Margin Ratio at PT Indocement Tunggal Prakarsa has significant effect on stock price, whereas Return on Equity and Earning per Share at the same company do not have significant effect on stoc price. Earning per Share, Return on Equity, and Operating Profit Margin at PT Holcim Indonesia Tbk. do not have ignificant effect. Therefore, it can be concluded that there are external factors influencing stock price at PT Indocement Tunggal prakarsa Tbk. and PT Holcim Indonesia Tbk. The example is global crisis 2008 originated in The United States presented impact on cement industry; the stock price of cement industry decreased then. Keywords:financial performance (EPS, ROA, and OPM); stock price at the end of the year